2008
DOI: 10.1007/s00249-008-0371-3
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis of prion protein by cathepsin S generates a soluble β-structured intermediate oligomeric form, with potential implications for neurotoxic mechanisms

Abstract: Formation of PrP aggregates is considered to be a characteristic event in the pathogenesis of TSE diseases, accompanied by brain inXammation and neurodegeneration. Factors identiWed as contributing to aggregate formation are of interest as potential therapeutic targets. We report that in vitro proteolysis of ovine PrP . This implies an important structural contribution of the 1 sequence within the globular domain of PrP. We propose that the removal or detachment of the 1 sequence enhances -oligomer formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…For example, Polyakova et al . (8) demonstrated that proteolysis of ovine rPrP by the cellular protease of cathepsin S generates the β‐structure oligomers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Polyakova et al . (8) demonstrated that proteolysis of ovine rPrP by the cellular protease of cathepsin S generates the β‐structure oligomers.…”
Section: Discussionmentioning
confidence: 99%
“…To design better strategies to treat prion diseases, it is crucial to identify the factors that promote the oligomerization process. Although many studies have focused on this topic (812), these experiments were commonly performed in simple buffer systems. The intracellular environment differs from these simplified conditions and is highly crowded because of the presence of high concentrations of soluble and insoluble macromolecules in the cytoplasm (13).…”
mentioning
confidence: 99%
“…Direct visualization of gangliosides and GPI-anchors in living cell membranes has been achieved using chemically synthetized fluorescent analogs and super-resolution STED microscopy (Eggeling et al, 2009; Polyakova et al, 2009; Komura et al, 2016; Suzuki et al, 2017). In 2009, Hell’s lab demonstrated that both Atto647N-conjugated GPI-anchors and GM1 have similar diffusion properties and confinements in rafts (called “trapping”; Eggeling et al, 2009).…”
Section: What Can Gangliosides Tell Us About Rafts?mentioning
confidence: 99%
“…Large, insoluble protein inclusions inside or outside cells were initially thought to be toxic. However, current evidence indicates that they are rather cytoprotective (Arrasate et al, 2004;Bodner et al, 2006), and that the smaller, more soluble protein dimers and oligomers are the ones that exert toxicity (Outeiro et al, 2007;Chen et al, 2009;Polyakova et al, 2009). Regardless of the exact mechanisms involved in each neurodegenerative disease, it is clear that alterations in normal protein homeostasis are central to this group of pathologies.…”
Section: Neurodegenerative Disorders As Protein Misfolding Pathologiesmentioning
confidence: 99%